Smoking status impacts treatment efficacy in smoke-induced lung inflammation: A pre-clinical study - Milad, Nadia; Pineault, Marie; Tremblay, Félix; Routhier, Joanie; Lechasseur, Ariane; Beaulieu, Marie-Josée; Aubin, Sophie; Morissette, Mathieu C. (Frontiers in Pharmacology, 2022)
Rationale: Smoking status and smoking history remain poorly accounted for as variables that could affect the efficacy of new drugs being tested in chronic obstructive pulmonary disease (COPD) patients. As a proof of concept, we used a pre-clinical model of cigarette smoke (CS) exposure to compare the impact of treatment during active CS exposure or during the cessation period on the anti-inflammatory effects IL-1α signaling blockade. Methods: Mice were exposed to CS for 2 weeks, followed by a 1-week cessation, then acutely re-exposed for 2 days. Mice were treated with an anti-IL-1α antibody either during CS exposure or during cessation and inflammatory outcomes were assessed. Results: We found that mice re-exposed to CS displayed reduced neutrophil counts and cytokine levels in the bronchoalveolar lavage (BAL) compared to mice exposed only acutely. Moreover, we found that treatment with an anti-IL-1α antibody during the initial CS exposure delayed inflammatory processes and interfered with pulmonary adaptation, leading to rebound pulmonary neutrophilia, increased BAL cytokine secretion (CCL2) and upregulated Mmp12 expression. Conversely, administration of anti-IL-1α during cessation had the opposite effect, improving BAL neutrophilia, decreasing CCL2 levels and reducing Mmp12 expression. Discussion: These results suggest that pulmonary adaptation to CS exposure dampens inflammation and blocking IL-1α signaling during CS exposure delays the inflammatory response. More importantly, the same treatment administered during cessation hastens the return to pulmonary inflammatory homeostasis, strongly suggesting that smoking status and treatment timing should be considered when testing new biologics in COPD.